Oksidentalisme Hasan Hanafi: (Konstruk Epistemologi Pengembangan Studi Islam) - kamaruddin Mustamin (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2021)
Hasan Hanafi's Occidentalism hinted at an epistemological framework for the development of Islamic studies. The birth of identityism is based on his ideals to establish a shared position between Islam and the West in a constructive-proportional dialogue of knowledge. The three agendas offered in the form of our attitude towards old traditions, our attitude towards Western traditions, and our attitude towards reality, are an epistemological construct of the development of systemically intertwined Islamic studies. Our attitude towards the old tradition with its steps tries to provide innovation in Islamic studies which basically has a strong historical footprint, our attitude towards Western traditions tries to arouse Muslims' awareness that addressing the West must be more proportional in its historical framework, while our attitude towards reality directs Islamic studies as a study that is not separated from the reality that surrounds it.